Profiling active phytochemical compounds of Ziziphus abyssinica herb responsible for antioxidant and antimicrobial activity - Nyaberi, M. O; Onyango, C. A; Mathooko, F. M; Maina, J. M; Makobe, M. (My University, 2017)
This paper seeks to determine the various active compounds that are present in the Ziziphus abyssinica A. Rich that would elicit antioxidant and antimicrobial activity on foodstuff. The cold methanolic extract was separated using TLC method, the activity of compounds was done using autobiographic TLC identification and the active areas were reconstituted and identified using GC-MS. There were 21 compounds which exhibited antioxidant activity with the most prevalent being Benzenamine, 3,4-dimethyl-, Phenol, 2,5-bis(1,1-dimethylethyl)-, Butylated hydroxytoluene, Methyl decanoate, Hexadecanoic acid / Palmitic acid and Phenol, 2,2'-methylenebis[6-(1,1-dimethylethyl)-4-ethyl-. Compounds with antimicrobial activity were 24 out of which some had antioxidant and antifungal. The most active compounds isolated were 2-Furancarboxaldehyde C5H4O2, 4-Methyl-2-hexanol, Sulphurous acid, cyclohexylmethyl undecyl ester, Decanoic acid (capric acid), Hydrazinecarboxamide, and N, N-diphenyl Aldehyde. It is therefore worth to note that AZA has antioxidant and antimicrobial properties that can qualify it to be a natural preservative.
Keywords: Bioautography; Antimicrobial; Antioxidant